2014
DOI: 10.1371/journal.pone.0097002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the NK1 Antagonist Emend Reduces Blood Brain Barrier Dysfunction and Edema Formation in an Experimental Model of Brain Tumors

Abstract: The neuropeptide substance P (SP) has been implicated in the disruption of the blood-brain barrier (BBB) and development of cerebral edema in acute brain injury. Cerebral edema accumulates rapidly around brain tumors and has been linked to several tumor-associated deficits. Currently, the standard treatment for peritumoral edema is the corticosteroid dexamethasone, prolonged use of which is associated with a number of deleterious side effects. As SP is reported to increase in many cancer types, this study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
2
19
0
1
Order By: Relevance
“…Importantly, this study revealed a relationship between the serum level of occludin and the severity of brain edema in patients with brain tumors. Previous investigations have con rmed that PBTE is vascular edema caused by damage to the BBB [17][18][19] . Occludin is an important component of the tight junctions that constitute the BBB.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, this study revealed a relationship between the serum level of occludin and the severity of brain edema in patients with brain tumors. Previous investigations have con rmed that PBTE is vascular edema caused by damage to the BBB [17][18][19] . Occludin is an important component of the tight junctions that constitute the BBB.…”
Section: Discussionmentioning
confidence: 96%
“…MMP-2 is usually located in the cytoplasm of tumor cells, and is often detected in the endothelial cells of the vascular basement membrane, thus suggesting that during the invasion of astrocytoma, MMP-2 and vascular endothelial growth factor have a synergistic role in regulating the angiogenesis of tumor vessels in MM (24,25). The structure of newly formed tumor vasculature is incomplete, and easily leaks, thus affecting the integrity of the blood-brain barrier (BBB); plasma and other macromolecules may penetrate into the cells through the damaged BBB and gather around the tumor, forming extensive peritumoral edema (26). Furthermore, MMP-2 may directly degrade the extracellular matrix of the basement membrane of blood vessels, loosening the structure, which is conducive to the invasion of tumor cells along the basement membrane (27).…”
Section: Discussionmentioning
confidence: 99%
“…and exerts an antitumor action [22,86]. Moreover, aprepitant activates the caspase-3 dependent apoptotic pathway by altering the expression of the apoptosis-related genes, increases the sensitization of certain tumor cells to the cytotoxic action of vincristine/arsenic trioxide (ATO) and decreases the expression of liver stemness markers blood-brain barrier permeability and brain water content [48,87,88].…”
Section: Acute Myeloid Leukemia: Sp/nk-1r System and The Nk-1r Antagomentioning
confidence: 99%